Enzymatic Inactivation of Oxysterols in Breast Tumor Cells Constraints Metastasis Formation by Reprogramming the Metastatic Lung Microenvironment - Moresco, Marta A.; Raccosta, Laura; Corna, Gianfranca; Maggioni, Daniela; Soncini, Matias; Bicciato, Silvio; Doglioni, Claudio; Russo, Vincenzo (Frontiers in Immunology, 2018)
Recent evidence indicates that immune cells contribute to the formation of tumor metastases by regulating the pre-metastatic niche. Whether tumor-derived factors involved in primary tumor formation play a role in metastasis formation is poorly characterized. Oxysterols act as endogenous regulators of lipid metabolism through the interaction with the nuclear Liver X Receptors-(LXR)α and LXRβ. In the context of tumor development, they establish a pro-tumor environment by dampening antitumor immune responses, and by recruiting pro-angiogenic and immunosuppressive neutrophils. However, the ability of LXR/oxysterol axis to promote tumor invasion and metastasis by exploiting immune cells, is still up to debate. In this study we provide evidence that oxysterols participate in the primary growth of orthotopically implanted 4T1 breast tumors by establishing a tumor-promoting microenvironment. Furthermore, we show that oxysterols are involved in the metastatic spread of 4T1 breast tumors, since their enzymatic inactivation mediated by the sulfotransferase 2B1b, reduces the number of metastatic cells in the lungs of tumor-bearing mice. Finally, we provide evidence that oxysterols support the metastatic cascade by modifying the lung metastatic niche, particularly allowing the recruitment of tumor-promoting neutrophils. These results identify a possible new metastatic pathway to target in order to prevent metastasis formation in breast cancer patients.